2021
DOI: 10.3390/nu13093148
|View full text |Cite
|
Sign up to set email alerts
|

Diet in Intestinal Fibrosis: A Double-Edged Sword

Abstract: The natural history of inflammatory bowel diseases, especially Crohn’s disease, is frequently complicated by intestinal fibrosis. Because of the lack of effective treatments for intestinal fibrosis, there is an urgent need to develop new therapies. Factors promoting intestinal fibrosis are currently unclear, but diet is a potential culprit. Diet may influence predisposition to develop intestinal fibrosis or alter its natural history by modification of both the host immune response and intestinal microbial comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Studies have also shown that intestinal adherent invasive Yersiniabactin generated by Escherichia coli (AIEC) has been found to induce granuloma and granulomatous colitis in vitro, which is directly linked to enteritis and intestinal fibrosis [ 14 ]. At present, there is universal concern that dietary habits and fiber have direct or indirect impacts on the intestinal tract, potentially altering the function of intestinal microbes [ 15 ].…”
Section: Current Viewpoint In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…Studies have also shown that intestinal adherent invasive Yersiniabactin generated by Escherichia coli (AIEC) has been found to induce granuloma and granulomatous colitis in vitro, which is directly linked to enteritis and intestinal fibrosis [ 14 ]. At present, there is universal concern that dietary habits and fiber have direct or indirect impacts on the intestinal tract, potentially altering the function of intestinal microbes [ 15 ].…”
Section: Current Viewpoint In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…Marion-Letellier et al, in their paper, indicate that following a high-fat (HF) diet may predispose to organ fibrosis. There is no confirmed effect of the HF diet on intestinal fibrosis, while there are mechanisms that could potentially lead to this condition due to the induction of the epithelial–mesenchymal transition (EMT) and Wnt-β-catenin [ 117 ]. Furthermore, the HF diet alters the signaling of peroxisome proliferator-activated receptor-γ (PPAR-γ) signaling, leading to disruption of epithelial integrity, thus altering the composition of the intestinal microbiota, which can trigger inflammation [ 118 ].…”
Section: Treatment Of Intestinal Fibrosismentioning
confidence: 99%
“…Therefore, a potential protective factor would be an anti-inflammatory diet rich in exogenous antioxidants such as flavonoids, vitamins, and minerals [ 125 , 126 ]. Furthermore, arginine and glutamine show potential antifibrotic effects [ 117 ].…”
Section: Treatment Of Intestinal Fibrosismentioning
confidence: 99%